Pajubá : o código linguístico da comunidade LGBT - Barroso, Renato Régis (2017)
This work presents an anthropological linguistic study, which proposes to analyze the spoken code used by the LGBT community, more precisely, the pajuba, originating from the contact between the Yoruba African language and the Portuguese language with a little use of French, English and Indian language. As an objective, our research aimed at the analysis of it as a linguistic code of resistance used by the homoaffective community, making a survey of the items that enter into its formation and its linguistic peculiarities; as well as to trace it way towards anthropology in order to show its importance in the process of the Bourgeois habitus. We also study their relationship with sociolinguistics in the process of euphemizing the pornographic phrases spoken by homosexuals, and how this code helps in the fight against homophobia. Data for the research were collected through individual and group interviews, experience reports and virtual polls with participants from the homosexual and heterosexual communities, ranging in age from 18 to 63 years. In the end, as results, we seek to prove the pajuba as a slang and its importance in the identity process of the LGBT community. Key-words: pajuba; slang; gay.